Psycho-social disruption, information disorder, and the politics of wind farming. (November 2018) - Marshall, Jonathan Paul
Abstract: Problems of methodology often involve informational and interpretative problems that also affect the social lives of the people being studied and analysed. As such, these problems are inherently important in analysis of those social lives. This paper explores how recognising the problems of informational disorder, or '(dis)information', allow us to elucidate the informational dynamics of the Australian Senate Committee Inquiry into Wind Turbines and the contested ways it attributes causality and distributes responsibility about possible illness. The Committee's reports and testimonies offer an almost overwhelming source of information about struggles over new forms of energy technology and the ways they become enmeshed in disorders of information, interpretation, politics and the relations of psycho-social disruption produced by climate change. The Committee members appear to be relatively active players in the process, aiming at particular outcomes, and ordering and disordering the information under review. Here we have a series of social events that are already politicised, disruptive, unintended and uncertain, yet treated, by actors, as clear and pre-determined certainties.